1989
DOI: 10.1159/000125288
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-Aspartic Acid Lesions of the Arcuate Nucleus in Adult C57BL/6J Mice: A New Model for Age-Related Lengthening of the Estrous Cycle

Abstract: We report a new effect of the excitotoxin N-methyl-aspartic acid (NMA) on adult mice. Besides confirming cell loss in the arcuate nucleus of animals treated as adults, we also observed lengthened estrous cycles. Cycling female C57BL/6J mice were treated with subcutaneous injections of NMA and estrous cycles monitored for 30 days. NMA treatment lengthened average estrous cycle length by 1 day, to 5.6 days. The elongated cycles were due to an increase in the frequency of 5- and 6-day cycles at the expense of 4-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Treatments will only become available if processes that trigger neuronal degeneration and death are understood and the endogenous compounds that prevent nerve cells from dying are identified [Peruche and Kreigelstein, 1993;Reiter et al, 19931. The recent neuropharmacological work on the actions of the major excitatory neurotransmitter in the CNS, the acidic amino acid L-glutamate, has contributed to the understanding of excitotoxic processes that finally lead to neuronal death [Dykens et al, 1987;Marani and Rietveld, 1987;May et al, 1989;Murphy et al, 1989;Pellegrini-Giampietro et al, 1990;Joseph et al, 1991;Wolf et al, 1991;Wozniak et al, 1991;Braun and Mahesh, 1992;Cheramy et al, 1992;Dawson and Wallace, 1992;Delbarre et al, 1992b;Kato et al, 1992;Kitamura et al, 1992;Pazdernik et al, 1992;Wenk et al, 1992;Zawia et al. 1992;ZS.-Nagy, 1992;Hall et al, 1993;Peruche and Kriegelstein, 19931. Melatonin and excitatory amino acids seem to have opposing roles regarding the developmental and aging processes [Marani and Rietveld, 1987;May et al, 1989;Braun and Mahesh, 1992;Reiter, 1992;Reiter et al, 19931.…”
Section: Neuronal Loss: the Pacemaker Of The Aging Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatments will only become available if processes that trigger neuronal degeneration and death are understood and the endogenous compounds that prevent nerve cells from dying are identified [Peruche and Kreigelstein, 1993;Reiter et al, 19931. The recent neuropharmacological work on the actions of the major excitatory neurotransmitter in the CNS, the acidic amino acid L-glutamate, has contributed to the understanding of excitotoxic processes that finally lead to neuronal death [Dykens et al, 1987;Marani and Rietveld, 1987;May et al, 1989;Murphy et al, 1989;Pellegrini-Giampietro et al, 1990;Joseph et al, 1991;Wolf et al, 1991;Wozniak et al, 1991;Braun and Mahesh, 1992;Cheramy et al, 1992;Dawson and Wallace, 1992;Delbarre et al, 1992b;Kato et al, 1992;Kitamura et al, 1992;Pazdernik et al, 1992;Wenk et al, 1992;Zawia et al. 1992;ZS.-Nagy, 1992;Hall et al, 1993;Peruche and Kriegelstein, 19931. Melatonin and excitatory amino acids seem to have opposing roles regarding the developmental and aging processes [Marani and Rietveld, 1987;May et al, 1989;Braun and Mahesh, 1992;Reiter, 1992;Reiter et al, 19931.…”
Section: Neuronal Loss: the Pacemaker Of The Aging Processmentioning
confidence: 99%
“…The recent neuropharmacological work on the actions of the major excitatory neurotransmitter in the CNS, the acidic amino acid L-glutamate, has contributed to the understanding of excitotoxic processes that finally lead to neuronal death [Dykens et al, 1987;Marani and Rietveld, 1987;May et al, 1989;Murphy et al, 1989;Pellegrini-Giampietro et al, 1990;Joseph et al, 1991;Wolf et al, 1991;Wozniak et al, 1991;Braun and Mahesh, 1992;Cheramy et al, 1992;Dawson and Wallace, 1992;Delbarre et al, 1992b;Kato et al, 1992;Kitamura et al, 1992;Pazdernik et al, 1992;Wenk et al, 1992;Zawia et al. 1992;ZS.-Nagy, 1992;Hall et al, 1993;Peruche and Kriegelstein, 19931. Melatonin and excitatory amino acids seem to have opposing roles regarding the developmental and aging processes [Marani and Rietveld, 1987;May et al, 1989;Braun and Mahesh, 1992;Reiter, 1992;Reiter et al, 19931. Excitatory amino acids act as sculptures and destroyers of neuronal networks, while melatonin seems to counteract these effects by preserving plasticity and protecting against over-stimulation of neurons, which leads to irreversible excitotoxicity and neuronal death due to oxidative stress [Marani and Rietveld, 1987;May et al, 1989;Joseph et al , 199 1 ;Naranjo-Rodriguez et al, 1991;Braun and Mahesh, 1992;Reiter et al, 19931.…”
Section: Neuronal Loss: the Pacemaker Of The Aging Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent autoradiographic stud ies suggest that kainate receptors are more abundant than NMDA receptors in the hypothalamus, and they have a different distribution. Most of the kainate binding sites are in the arcuate nucleus-median eminence region [5][6][7], while NMDA sites appear to be localized in the preoptic area [8]. These results are supported by data showing that non-NMDA receptor agonists are more effective at stimu lating GnRH release from arcuate nucleus-median emi nence fragments [9], while NMA is more potent at stimu lating release from the medial basal hypothalamus [ 10], In this study, we compare NMA and kainate responses dur ing lactation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, NMDA receptors in the monkey hypothalamus, as revealed autoradiographically by MK801 labelling, are diffusely and less densely distributed throughout the medial basal hypo thalamus [22]. A similar distribution of NMDA and non- 664 Medhamurthy/Gay/Plant Glutamate Receptors and GnRH Release NMDA receptor binding in rodent hypothalamus has previously been reported [23][24][25]. In this regard, it is of interest to note that in vitro studies with hypothalamic fragments from rat have demonstrated KA induced GnRH release [26,27], and that a decrease in GnRH re sponsiveness to intermittent intravenous administration of KA, similar to that reported here for the monkey, has also been recently observed in the adult female rat [Abbud and Smith, unpubl.…”
Section: Discussionmentioning
confidence: 66%